Charlie Brown's 'Cyclopedia, v.7 : featuring space travel. - Schulz, Charles (New York : Funk and Wagnalls, 1980)
Super Questions and answers and amazing facts
"Based on the Charles M. Schulz Characters"--Snoopy
Keywords: Cyclopedias; Planets -- Juvenile literature